MOTIVASI CINA MENJALIN KERJASAMA DENGAN UNI EROPA DALAM PROGRAM NEAR ZERO EMISSIONS COAL (NZEC) 2007-2013 - Yuning Nur Asri; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research discusses about the motivation of China’s cooperation with European Union in the Near Zero Emission Coal program. Economic development is a major priority of the Chinese government with promote industrialization. The industrial sector plays an important role in improving the economic growth of China. Economic development is a major priority of the Chinese government with promote industrialization. The industrial sector plays an important role in improving economic growth of China. However industrial activity resulted in environmental degradation with increasing carbon emissions as the increase in energy consumption of coal. In the middle a dilemma of development, the Chinese government cooperating with the EU, which feared to disturb China's economic development.The author analyzes this case use qualitative methods that collects data and facts through some literature. This research uses the dependence theory by Theotonio Dos Santos, structuralism perspective and the concept of economic relations and the environment. The results of this research shows there are some China’s motivations to cooperate with European Union in the Near Zero Emissions Coal (NZEC) program are the interests of Capture Carbon and Strorage’s technology transfer, capital and markets in Europe. Motivations that lead to China depending on the European Union, especially the dependence of capital and technology industries. This cooperation has entered the third phase is to construct the development of CCS technology in power plants in China.Keywords : Dilemma of Development, Motivation, Near Zero Emissions Coal Program, Transfer of Carbon Capture and Strorage’s Technology.